Prevalence of Trichomonas vaginalis, Mycoplasma genitalium and Ureaplasma urealyticum in men with urethritis attending an urban sexual health clinic. (May 2015) - Khatib, N; Bradbury, C; Chalker, V; Koh, GCKW; Smit, E; Wilson, S; Watson, J
We conducted a study to determine the prevalence of Trichomonas vaginalis (TV), Mycoplasma genitalium (MG) and Ureaplasma urealyticum (UU) in men with urethritis, attending an urban sexual health clinic, in order to inform screening and treatment policies. Men attending an urban sexual health clinic between June 2011 and January 2012 were evaluated. Urine samples were collected from men with urethritis and tested for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (GC) and TV using transcription-mediated amplification and for MG and UU using polymerase chain reaction. Eighty-three samples were analysed. The prevalence of CT was 33.7% (28/83), GC was 16.8% (14/83), TV was 3.6% (3/83), MG was 12.0% (10/83) and UU was 4.8% (4/83). Fifteen men had recurrent urethritis. Of these, three were found to have had TV, five to have had MG and none to have had UU, at initial presentation. Given the prevalence of MG in this study, there is an urgent need for further larger studies looking at optimal treatment regimens and screening strategies in urethritis.